ANALYTIC FUNCTIONS OF THE STABILITY OF SUBGRADE OBJECTS - Hritsyk, V. I. (Science and Transport Progress, 2003)
The functions of the intense condition, durability and the stability describing stability of the subgrade, algorithms of their optimization and definition are considered in the article.